Biological Control in Bolivia - Franco, Javier P.; Crespo, Luis V.; Colmenarez, Yelitza C. [UNESP]; van Lenteren, Joop C.; VanLenteren, J. C.; Bueno, VHP; Luna, M. G.; Colmenarez, Y. C. (Cabi Publishing-c A B Int, 2020)
A number of introductions of parasitoids and predators were carried out in the 1950s for classical biological control of olive scale, woolly apple aphid, white peach scale, Mediterranean fruit fly and Anastrepha fruit fly, with control of cottony cushion scale by the coccinellid Rodolia being a particular success. In 1963, dipteran natural enemies were introduced for the control of sugarcane borers, Diatraea spp. Since 1963 native hymenopteran and dipteran parasitoids have been field collected and re-released for control of the borers. In 1969 an IPM programme of sugarcane borers was started, and biocontrol in sugarcane in the period 1970-2000 mainly consisted of augmentative releases of hymenopteran and tachinid parasitoids. Another successful IPM programme dealt with control of potato moth species with a product - now commercially available - that contains a native strain of the granulosis virus Baculovirus phthorimaea and a native strain of Bacillus thuringiensis. Coffee berry borer was brought under biocontrol in the 1990s by releasing a hymenopteran parasitoid and application of an entomopathogenic fungus. An increased demand for organic products since 2000 has stimulated work on isolation, characterization, mass production, formulation and certification of a number of microbial control agents. These are used in many crops and examples are microbial control of pest in potato and quinoa. Many of the quinoa pests are kept under natural control by predators and parasitoids, which has been well documented during the past 10 years. Currently most pests in sugarcane and soybean are under a combination of natural, augmentative and classical biocontrol.